Choreography invisible the disappearing work of dance - Pakes, Anna ca. 20./21. Jh (Oxford studies in dance theory, 2020)
Focusing on Western theatre dance, Choreography Invisible explores the metaphysics of dances and choreographic works. It draws on a range of resources from analytic philosophy of art to develop the argument that dances are repeatable structures of action. The book also analyses the idea of the dance work in long-term historical perspective. Tracing different ways in which dances have been conceptualised across time, the book considers changing notions of authorship, fixity, persistence, and autonomy from the fifteenth century to the present day.